2014
DOI: 10.1080/10615806.2014.954244
|View full text |Cite
|
Sign up to set email alerts
|

Memories of Holocaust-related traumatic experiences, sense of coherence, and survivors' subjective well-being in late life: some puzzling findings

Abstract: The results of the present study provide support for Antonovsky's salutogenic perspective. It is highly plausible that survivors who underwent severe experiences during the Holocaust period were forced to call upon all their inner strengths and coping resources,and that their success in doing so and also surviving this horrendous period, might have contributed to the development of a stronger sense of meaning and coherence, which, in turn lead to a better sense of mental health as they approach the final seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similarly, Zeidner and Aharoni-David (2014) found indirect effects of SOC in the relationship between memory traces of specific traumatic experiences of Holocaust survivors and adaptive outcomes. They concluded that the horrors of the Holocaust recruited the survivors' inner strengths and coping resources, which in turn contributed to the development of a stronger sense of meaning and coherence, improving a better sense of mental health.…”
Section: Family Climate Factorsmentioning
confidence: 99%
“…Similarly, Zeidner and Aharoni-David (2014) found indirect effects of SOC in the relationship between memory traces of specific traumatic experiences of Holocaust survivors and adaptive outcomes. They concluded that the horrors of the Holocaust recruited the survivors' inner strengths and coping resources, which in turn contributed to the development of a stronger sense of meaning and coherence, improving a better sense of mental health.…”
Section: Family Climate Factorsmentioning
confidence: 99%
“…Bar-Tur et al [ 146 ] found that past traumatic losses had an impact on well-being in the aging; however, while Holocaust losses had a negative impact, traumatic personal losses had a positive impact. Zeidner and Aharoni-David [ 185 ] found no evidence for the moderating or “buffering” effect of survivors’ sense of coherence (SOC), but supported indirect impacts of SOC on the relationship between memory traces of precise traumatic experiences and adaptive effects; it is very likely that survivors who had painful experiences throughout the Holocaust had to use their strength and coping ability and that prevailing during those horrific years, might have led to a more powerful feeling of meaning and coherence, leading to a greater sense of mental health as they grew old.…”
Section: Discussionmentioning
confidence: 99%
“…Reminiscence and life review interventions aimed to strengthen the patients' sense of coherence (SOC). Indeed, SOC was found to mediate the association between past traumas and posttraumatic symptoms in later life (van der Hal-van Raalte et al, 2008;Fossion et al, 2014;Schäfer et al, 2019;Zeidner & Aharoni-David, 2015). Maercker and Müller (2004) emphasize the role of interpersonal factors ("social acknowledgement"; "disclosure") in coping with trauma.…”
Section: Structured Life Reviewmentioning
confidence: 99%